Solitude in creative process. Creativity in pandemic - Grabowska-Nogala, Anna (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
Based on the scientific literature and the results of the research conducted by the author, the first part of the article deals with the topic of loneliness, different ways of defining it and its relationship with the creative process. The second part focuses on presenting the phases of the creative processes of professional artists researched by the author, as well as creativity during the lockdown period caused by the coronavirus pandemic. It describes the process of creating a professional choreographer who, despite the limitations, realized his ballet performance.